EVALUATION OF VILLAGE FUND MANAGEMENT IN INCREASING TOURISM DEVELOPMENT IN GALANTI VILLAGE, WOLOWA DISTRICT, BUTON REGENCY - Lukman, Lukman; Asiri, La; Srimayunita, Srimayunita (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
The objective of this study is to assess the effectiveness of the management of the Village Fund in promoting the development of tourism in Galanti Village, Wolowa District, Buton Regency. The research methodology employed in this study is qualitative research, which focuses on identifying key informants who possess substantial information relevant to the research objectives. The data collection techniques utilized include interviews, observations, and documentation. The study employs an interactive paradigm for data analysis, which involves three distinct steps: data reduction, data display, and data verification leading to the drawn result. The study's findings revealed that the evaluation of village fund management in enhancing tourism development in Galanti Village, Wolowa District, Buton Regency yielded satisfactory results in terms of indicators such as efficiency, adequacy, responsiveness, and accuracy. However, the results were unfavorable in terms of leveling indicators, primarily due to the lack of transparency in the allocation and management of village funds. Consequently, the development of tourism in Galanti Village, Wolowa District, Buton Regency was uneven.